Induction of apoptosis and hypoxic stress in malignant melanoma cells via graphene-mediated far-infrared radiation - Wumei Zhao; Ziwen Chen; Wenxing Fu; Chenyan Ye; Haijing Fu; Tianyi Xu; Binghui Wu; Lina Chen; Shi-Jun Shan (BMC Cancer)
Abstract Background Malignant melanoma (MM) is a highly aggressive skin tumor with a rising incidence and poor prognosis. Although current clinical treatments, including surgery, targeted therapy, immunotherapy, and radiotherapy, have shown some efficacy, therapeutic options remain limited for elderly patients and those with metastatic disease, highlighting the urgent need for novel therapeutic strategies. In recent years, the unique far-infrared radiation (FIR) properties of graphene have demonstrated potential applications in cancer treatment. However, the mechanisms underlying FIR’s effects in MM therapy remain poorly understood. Methods This study systematically evaluated the inhibitory effects of FIR on MM through in vitro cell experiments, animal models, and molecular mechanism analysis. First, the B16F10 melanoma cell line was used as the experimental model. The effects of FIR on cell proliferation, apoptosis, and the cell cycle were assessed using CCK-8 assays and flow cytometry, while RNA sequencing was conducted to analyze the associated signaling pathways. Second, specific caspase inhibitors were employed to further validate the mechanisms of FIR-induced apoptosis. Finally, a syngeneic tumor transplantation model in C57BL/6J mice was established to comfirm the anti-tumor efficacy of FIR in vivo, thereby comprehensively elucidating its anti-cancer mechanisms. Results The results demonstrated that FIR significantly inhibits MM. In vitro experiments revealed that FIR treatment markedly suppressed B16F10 cell proliferation, induced apoptosis, caused G0/G1 phase cell cycle arrest, and downregulated the expression of hypoxia-related proteins such as HIF-1α. In animal studies, FIR significantly inhibited tumor growth. RNA sequencing revealed that FIR exerts its anti-cancer effects through multiple signaling pathways. Notably, the use of caspase inhibitors Z-DEVD-FMK and Z-LEHD-FMK, which specifically inhibit caspase-3 and caspase-9, respectively, can rescue cells from apoptosis induced by FIR treatment. Conclusion This study systematically elucidated that FIR exerts anti-tumor effects through multiple mechanisms, including inducing MM cell apoptosis, exacerbating hypoxic stress, and causing cell cycle arrest. The findings provide new insights and approaches for MM treatment and establish a theoretical foundation for the clinical application of FIR in cancer therapy.